Self-microemulsifying system of an ethanolic extract of Heliopsis longipes root for enhanced solubility and release of affinin - Dailenys Marrero-Morfa; César Ibarra-Alvarado; Francisco J. Luna-Vázquez; Miriam Estévez; Eremy Miranda Ledesma; Alejandra Rojas-Molina; Carlos T. Quirino-Barreda (SpringerOpen, 2023)
Abstract Self-microemulsifying or self-nanoemulsifying drug delivery systems (SMEDDS/SNEDDS) are well known to improve the dissolution and increase the oral bioavailability of hydrophobic drugs, including herbal extracts. Organic extracts of Heliopsis longipes root and affinin, its main component, induce a vasodilator effect; however, they are poorly water soluble and therefore are difficult to administer and dose by the oral route. This research aimed to develop, through pseudo-ternary phase diagrams, a self-microemulsifying system prepared from an ethanolic extract of H. longipes root (HL-SMDS). In addition, the optimized lipid-based formulation was characterized and its in vitro gastrointestinal simulated dissolution was determined. The formulation composed of Transcutol, 55% (solubilizer); Tween80/PG, 10% (surfactant/co-solvent); Labrasol, 35% (surfactant); and the herbal extract was selected as optimal and identified as a SMEDDS, since when coming into contact with water, it forms a micro-emulsion with droplet sizes less than 100 nm. The stability tests showed that HL-SMDS remained stable over time under extreme conditions. Furthermore, the amount of affinin released from HL-SMDS at pH 1 and 6.8 was higher than that of the ethanolic extract from H. longipes root. These results indicate that HL-SMDS is a novel alternative to improve the aqueous solubility and therefore the oral bioavailability of the ethanolic extract of H. longipes root.